A Leukocyte Score to Improve Clinical Outcome Predictions in Bacteremic Pneumococcal Pneumonia in Adults. (2nd September 2014) - Blot, Mathieu; Croisier, Delphine; Péchinot, André; Vagner, Ameline; Putot, Alain; Fillion, Aurélie; Baudouin, Nicolas; Quenot, Jean-Pierre; Charles, Pierre-Emmanuel; Bonniaud, Philippe; Chavanet, Pascal; Piroth, Lionel
Abstract : In multivariate analysis, a leukocyte score that adds 1 point each for neutropenia, lymphopenia and monocytopenia was associated with 30-day mortality in 192 patients with bacteremic pneumococcal pneumonia. By reflecting immunoparalysis, this score could improve clinical outcome predictions in BPP. Abstract: Background. Bacteremic pneumococcal pneumonia (BPP) is associated with high and early mortality. A simple procedure to predict mortality is crucial. Methods. All adult patients with BPP admitted from 2005 through 2013 to the University Hospital of Dijon, France, were enrolled to study 30-day mortality and associated factors, particularly leukocyte counts. A simple leukocyte score was created by adding 1 point each for neutropenia (<1500 cells/mm 3 ), lymphopenia (<400), and monocytopenia (<200). Results. One hundred and ninety-two adult patients (mean age, 69 years; standard deviation [SD], 19 years) who had developed and were hospitalized for BPP (58% community-acquired) were included. The 30-day crude mortality rate was 21%. The mean Pneumonia Severity Index score was high at 127.3 (SD = 41.3). Among the 182 patients who had a white blood cell count, 34 (19%) had a high leukocyte score (≥2). Multivariate analysis revealed that mortality was significantly associated with a high leukocyte score (odds ratio, 6.28; 95% confidence interval, 2.35–16.78), a high respiratory rate, a low serum bicarbonate level, and an altered mental status (all P < .05). The leukocyte score was not significantly dependent on the previous state of immunosuppression, alcoholism, or viral coinfection, but it did correlate with an acute respiratory distress syndrome and a low serum bicarbonate level. Conclusions. This new leukocyte score, in combination with the well known predictive factors, seems of interest in predicting the risk of death in BPP. A high score correlated with organ dysfunction and probably reflects the level of immunoparalysis. Its predictive value has to be confirmed in other cohorts.